In situ conservation of the wild relative of the common bean (Phaseolus vulgaris var. aborigineus) at the south of its neotropical distribution: environmental characterization of a population in central Argentina - Sirolli, Horacio (2015)
The common bean (Phaseolus vulgaris L.) is a food of worldwide vital importance. Like any crop, the conservation of its wild relatives is essential to maintain the genetic variability needed for plant breeding. In situ conservation of such population has the additional benefit of generating new variations through the evolution of its natural environment. In 2004, wild populations of P. vulgaris var. aborigineus were found in the province of Córdoba (Argentina), being the southernmost specimen of its current distribution. In order to study the state and characterize the environment of such populations, vegetation censuses were conducted along a stretch of the Tanti stream-arroyo Tanti-(Punilla, Córdoba). Results showed that the wild bean has an intermediate to high constancy throughout the watercourse and its presence decreases upstream and away from the stream. Most cover took place in plots with scarce slope, high incidence of light and intense magnitude of floods. Vegetation develops in an environment surrounded by forests, meadows and intermediate physiognomy. Besides adventitious species, the studied area still has native species of high conservation value. Based on the analysis of this work, and considering the biogeographical significance of this population of wild bean, we conclude that this stretch of the studied stream is a priority area for the in situ conservation of P. vulgaris var. aborigineus.